Data quality evaluation of electronic health records in the hospital admission process - Duarte, Júlio (2010)
Data Quality Evaluation is a critical problem, specially in Healthcare, where people may take decisions based on confident, acceptable and secure information. In this paper we show how data quality can be evaluated from electronic health records, in particular in a hospital setting. We construct a dynamic virtual world of complex entities or agents, driven by one criterion alone, intelligence, for the provision of healthcare. This virtual world will witness the emergence and will be based on a versatile and powerful paradigm, where the candidate solutions (here understood as agents) are seen as evolutionary logic programs or theories, being the test if a solution is optimal based on a measure of the quality-of-information that stems from them.